Diffuse advanced hepatocellular carcinoma after HCV eradication in an HIV-infected patient: A unique complete response to sorafenib - Gonçalo Nunes; Cristina Fonseca; Marta Patita; Mario João Aleixo; Miguel Ramalho; Jorge Fonseca; Jorge Fonseca (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Nunes G, Fonseca C, Patita M, Aleixo MJ, Ramalho M, Fonseca J. Diffuse advanced hepatocellular carcinoma after HCV eradication in an HIV-infected patient: A unique complete response to sorafenib. Turk J Gastroenterol 2020; 31(2): 184-6.